Effect of UV Irradiation (A and C) on Casuarina equisetifolia-Mediated Biosynthesis and Characterization of Antimicrobial and Anticancer Activity of Biocompatible Zinc Oxide Nanoparticles - Amna Komal Khan; Sullivan Renouard; Samantha Drouet; Jean-Philippe Blondeau; Iram Anjum; Christophe Hano; Bilal Haider Abbasi; Sumaira Anjum (MDPI AG, 2021)
The green synthesis of nanoparticles has emerged as a simple, safe, sustainable, reliable and eco-friendly protocol. Among different types of NPs, green-synthesized zinc oxide NPs (ZnONPs) show various promising biological uses due to their interesting magnetic, electrical, optical and chemical characteristics. Keeping in view the dependence of the therapeutic efficacy of NPs on their physico-chemical characteristics, the green synthesis of ZnONPs using Casuarina equisetifolia leaf extract under UV-A and UV-C light was carried out in this study. UV-irradiation helped to control the size and morphology of ZnONPs by exciting the electrons in the photoactive compounds of plant extracts to enhance the bio-reduction of ZnO into ZnONPs. C. equisetifolia leaf extract was found enriched with phenolic (2.47 ± 0.12 mg GAE/g DW) and flavonoid content (0.88 ± 0.28 mg QE/g DW) contributing to its 74.33% free-radical scavenging activity. FTIR spectra showed the involvement of polyphenols in the bio-reduction, stabilization and capping of ZnONPs. Moreover, SEM-EDX and XRD analyses showed great potential of UV-C light in yielding smaller (34-39 nm) oval-shaped ZnONPs, whereas UV-A irradiation resulted in the formation of fairly spherical 67-71 nm ZnONPs and control ZnONPs were of mixed shape and even larger size (84-89 nm). Green-synthesized ZnONPs, notably CE-UV-C-ZnONPs, showed promising anti-bacterial activities against Bacillus subtilis, Pseudomonas fluorescens and Pseudomonas aeruginosa. Moreover, ZnONPs also enhanced ROS production which led to a significant loss of mitochondrial membrane potential and activated caspase-3 gene expression and caspase-3/7 activity in human hepatocellular carcinoma (HepG2) cells. CE-UV-C-ZnONP treatment reduced HepG2 cell viability to as low as 36.97% owing to their unique shape and smaller size. Lastly, ZnONPs were found to be highly biocompatible towards brine shrimp and human red blood cells suggesting their bio-safe nature. This research study sheds light on the plausible role of UV radiation in the green synthesis of ZnONPs with reasonable control over their size and morphology, thus improving their biological efficacy.